Birth preparation acupuncture for normalising birth: An analysis of NHS service routine data and proof of concept. (16th November 2020) - Lokugamage, A. U.; Eftime, V. A. I.; Porter, D.; Ahillan, T.; Ke, S. X.
Abstract: A number of studies show that acupuncture may help with labour and delivery. An NHS maternity acupuncture service providing birth preparation acupuncture has assessed its routine hospital maternity annual data from 2014 to 2016 to see what effect it had on labour and delivery outcomes. The data from this service was analysed and women who had birth preparation acupuncture were compared with those who did not receive it. Maternal age, parity and socio-economic status were considered confounders and were adjusted for in the analysis. Women who received acupuncture had more normal births (less surgical births) [OR 0.76 (0.64, 0.91)], required less intrapartum analgesia [OR 0.74 (0.63, 0.86)], fewer components of an induction of labour [OR 0.74 (0.61, 0.91)] and a reduced length of a hospital stay [OR 0.91 (0.87, 0.95)]. The patients highly valued the availability of acupuncture within the maternity service as it enhanced their patient journey. Impact statement: What is already known on this subject? Numerous studies provide evidence for the effects of acupuncture in normalising pregnancy and birth. These effects include musculoskeletal preparation of the pelvis, cervical ripening, enhancing endogenous oxytocin release, and analgesic properties. What do the results of this study add? Our analysis shows that women who received birth preparation acupuncture had fewer surgical births, required less intrapartum analgesia, less components of induction of labour and had a reduced length of hospital stay, supporting the use of maternity acupuncture in normalising birth outcomes. What are the implications of these findings for clinical practice and/or further research? The findings show that acupuncture, by potentially normalising birth, may lead to reductions in costs of service. Further, additional research is required to see whether acupuncture is cost effective and could have an adjunctive role as a complementary therapy for improving birth outcomes and a woman's experience of childbirth.